THE EFFECT OF PRESSURE CONVECTION AND UNSTEADY FRICTION ON THE STRUCTURE OF A SHOCK PULSE - Lukianov , Pavlo (Problems of Friction and Wear, 2026)
Unsteady fluid flow refers to those that generate a shock pulse, which is usually called a water hammer. Despite the fact that many works are devoted to this topic, there are still no works that consider such interesting properties of the flow as its self-similarity at the initial moments of time when the shock pulse is formed - taking into account the physical phenomena indicated in the title of the work. This is especially important for the correct physical description phenomena using modern 3-D modeling and calculation tools, since the nonlinearity of the system can become a source of significant deviations of the numerical solution from the exact one. In this work, attention is paid to the influence of unsteady friction of the fluid against the pipe wall (Bruno-Vitkovsky model) and convection of the pressure disturbance field, as well as their combined action. Among the main results of the work, the following should be noted: neither the influence of convection nor the influence of unsteady friction can be neglected; each of the just mentioned physical mechanisms and both together lead to a significant spatial expansion of the region of disturbances from the shock pulse. Another result is that the dimensionless distributions of the shock pulse propagation velocity field and pressure disturbances asymptotically coincide with each other, and without taking into account the convection of the pressure field, these (dimensionless) solutions are equal everywhere.